Effect of Zr incorporation on microstructure and properties of magnetron sputtered RuZr thin films. (September 2020) - Meng, Yu; Song, Zhongxiao; Li, Yanhuai; Hu, Wei
Abstract: RuZr thin films with different Zr content were deposited on p-type Si (100) substrates by co-sputtering from Ru and Zr targets. The effect of Zr doping on the composition, microstructure and properties of RuZr films were investigated in detail. Both Ru and Zr atoms are mainly in metallic state and no reaction occurred between the two elements. The film microstructure is altered gradually from nanocrystalline to amorphous state with the increasing Zr content. When the Zr content is 17.72%, the RuZr alloy film exhibits low resistivity and good thermal stability. Hence, the introduction of Zr can inhibit the crystallization of Ru film and make prospects of amorphous RuZr film for the application as a diffusion barrier in Cu interconnection. Highlights: The elevated Zr content in RuZr films leads to different crystallization behavior of the films. Both Ru and Zr atoms are mainly in metallic state and no reaction occurred between the two elements. RuZr films with optimized Zr content could be a promising diffusion barrier for advanced Cu interconnection.